TUBERCULOSIS IN THE PENITENTIARY SYSTEM IN THE COUNTRIES OF EUROPE AND THE RUSSIAN FEDERATION - I. A. Vasilyeva; S. A. Sterlikov; E. M. Belilovsky; S. E. Borisov; S. B. Ponomarev (Туберкулез и болезни лёгких, 2018)
The article presents the data on the prevalence of tuberculosis in the penitentiary units in the countries of the WHO European Region compared to theRussian Federation.It lists factors providing an impact on the risk of the disease and notification rate of tuberculosis cases in prisons.Monitoring of tuberculosis in the penitentiary units is described including the formation of notification rates and treatment outcomes. It presents information on the comparatively high quality of tuberculosis monitoring in the penitentiary units of theRussian Federation.Potential causes of differences between the incidence of tuberculosis in different countries of the WHO European Region are analyzed.